Comparison of multi-temporal and multi-methodical aquatic environmental assessments (on the example of the Pripyat River for 1999 and 2022) - Fedorovskyi, Oleksandr; Khyzhniak, Anna; Tomchenko, Olga; Bondarenko, Alla (Ukrainian journal of remote sensing, 2023)
The article uses the example of the Pripyat River to examine the methodological features and conditions for comparing multi-temporal and multi-methodological (obtained by different methods) assessments of the ecological state of the aquatic environment. Thus, when comparing the current ecological state (for 2022) of the Prypiat River, obtained by the statistical criterion (SC) method with the ecological state of the river in 1999, obtained by the method of aquatic plant groups (APG), it is proposed to form virtual standards of the SC method on the basis of reference sites of previous assessments of the ecological state of the river (1999). A comparison of the ecological state of the Pripyat River in 2022 and 1999 showed significant changes in the structure of water quality in 2022 compared to 1999, namely a decrease in dirty areas and an increase in moderately polluted and clean areas. The study confirms the validity of the proposed method of comparing multi-temporal and multi-methodological aquatic environmental assessments.